Impregnation liquid for iron-based alloy magnetic powder core and impregnation method based on impregnation liquid
By using the impregnation liquid of a specific formula, the iron-based alloy magnetic powder core is impregnated twice, forming a composite film and bonding it to nano-silicon oxide, the problems of low strength and degradation of magnetic properties of the combined magnetic circuit core are solved, and the strength and magnetic properties are significantly improved.
Patent Information
- Application Number
- CN202510143725.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-10
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2045-02-10
AI Technical Summary
The existing combined magnetic circuit core strength is low, the magnetic performance decreases after impregnation treatment, and the core will affect the appearance after the glue is overflowed.
The impregnation solution containing 5~15% metal organic compound, 5~20% resin and 65~90% organic solvent was used to impregnate the iron-based alloy magnetic powder core twice to form a composite film and bond it to nano-silicon oxide to improve the density and stability of the insulating film.
The strength and magnetic properties of the iron-based alloy magnetic powder core are significantly improved, and the appearance problems and magnetic properties are avoided due to resin residues.
Smart Images

Figure CN119588928A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an impregnation liquid for an iron-based alloy magnetic powder core and also relates to an impregnation method based on the impregnation liquid, belonging to the technical field of magnetic materials. Background Art
[0002] Iron-based alloy magnetic powder core is a soft magnetic composite material prepared by powder metallurgy process. Common ones include iron powder core, iron silicon powder core, iron nickel powder core and iron silicon aluminum powder core. Due to its advantages of high magnetic permeability, high saturation magnetic induction intensity and high frequency stability, it is widely used in high-performance electronic components such as inductors, photovoltaic inverters and active filters. However, as electronic devices continue to develop in the direction of high frequency, high efficiency, miniaturization and integration, the requirements for iron-based alloy magnetic powder cores are getting higher and higher. However, the traditional magnetic ring structure in the iron-based alloy magnetic powder core can no longer meet the actual market demand, and the advantages of combined magnetic circuit devices have gradually emerged. However, while the combined magnetic circuit devices are developing rapidly, there are also difficult problems, especially the strength of the combined magnetic circuit core. Since the traditional ring structure will be sprayed after the magnetic core is processed, the strength of the magnetic core after spraying can be better guaranteed than that of the combined magnetic core exposed to the outside, so improving the strength of the combined magnetic circuit core is the key to the wide application and stable operation of the combined magnetic circuit devices.
[0003] At present, the strength of the combined magnetic circuit core is improved by impregnation treatment. The impregnation liquid used in the impregnation treatment is obtained by dissolving resin in an organic solvent. The impregnation treatment process is to immerse the iron-based alloy magnetic powder core in the impregnation liquid. However, the strength improvement of the combined magnetic circuit core by the above method is limited. If the core strength is improved by extending the impregnation time and increasing the concentration of the impregnation liquid, resin will remain on the surface of the treated product, which will seriously affect the appearance of the core and greatly deteriorate the magnetic properties of the product. Summary of the invention
[0004] Purpose of the invention: The purpose of the present invention is to provide an impregnation liquid for iron-based alloy magnetic powder cores; another purpose of the present invention is to provide an impregnation method based on the above-mentioned impregnation liquid. The iron-based alloy magnetic powder core obtained by the method of the present invention can greatly improve the strength of the formed combined magnetic circuit core while also improving its magnetic properties, thereby solving the problems of low strength of the existing combined magnetic circuit core, decreased magnetic properties after impregnation treatment, and appearance affected by glue overflow of the magnetic core.
[0005] Technical solution: The impregnation liquid for the iron-based alloy magnetic powder core of the present invention is prepared from the following components in percentage by mass: 5-15% of a metal organic compound, 5-20% of a resin and 65-90% of an organic solvent.
[0006] Wherein, the metal organic compound is one of ferric hydroxide, cobalt acetate or nickel acetate.
[0007] Wherein, the resin is one of epoxy resin, phenolic resin or polyester resin.
[0008] Wherein, the organic solvent is one of methanol, ethanol or acetone.
[0009] The impregnation method based on the above impregnation liquid comprises the following steps: (1) The iron-based alloy powder before insulation is immersed in the impregnation liquid, and then dried to obtain the iron-based alloy powder after impregnation; the particle size D50 of the iron-based alloy powder is generally 30~60μm; (2) insulating the iron-based alloy powder of step (1) with a nano-silicon oxide dispersion, pressing and annealing the iron-based alloy magnetic powder core after the insulation treatment (the iron-based alloy magnetic powder core is prepared by a powder metallurgy process), washing and drying the obtained iron-based alloy magnetic powder core, and obtaining the iron-based alloy magnetic powder core to be impregnated; (3) completely immersing the iron-based alloy magnetic powder core of step (2) in the impregnation liquid, and then washing it; (4) The cleaned iron-based alloy magnetic powder core is heated and solidified, and then naturally cooled to obtain an impregnated iron-based alloy magnetic powder core.
[0010] Wherein, in step (1), the soaking temperature is 40-80°C, and the soaking time is 20-60 min (heating can accelerate molecular motion and promote film formation); the drying temperature is 60-120°C, and the drying time is 30-60 min.
[0011] Wherein, in step (2), the amount of nano-silicon oxide dispersion added is 10-16‰ of the mass of the iron-based alloy powder.
[0012] Wherein, the mass concentration of the nano-silicon oxide dispersion is 4 g / L.
[0013] Wherein, in step (2), acetone is used for cleaning, and the cleaning time is 10-15 minutes; and the drying temperature is 60-120°C.
[0014] Wherein, in step (3), the soaking time is 2 to 6 hours, and the soaking temperature is 40 to 80°C; acetone is used for cleaning, and the cleaning time is 30 to 60 minutes.
[0015] Wherein, in step (4), the heating time is 2 to 6 hours, and the heating temperature is 120°C to 350°C.
[0016] Beneficial effects: Compared with the prior art, the present invention has the following significant effects: (1) The impregnation liquid of the present invention contains a metal organic compound in the formula. During the impregnation process of the iron-based alloy magnetic powder particles, the metal organic compound and the resin can form a composite film (resin and metal chelate film) on the surface of the iron-based alloy magnetic powder particles. On the one hand, it can effectively prevent the resin (adhesive substance) from volatilizing during the subsequent annealing process. On the other hand, the composite film can be bonded with nano-silicon oxide, thereby improving the density and stability of the insulating film, and further improving the coating effect of the insulating film on the iron-based alloy magnetic powder particles; at the same time, during the impregnation process of the iron-based alloy magnetic powder core, the impregnation liquid of the present invention has good permeability and excellent high-temperature curing effect, thereby achieving full protection of the iron-based alloy magnetic powder particles and the iron-based alloy magnetic powder core, and achieving the purpose of significantly improving the strength of the iron-based alloy magnetic powder core; (2) The impregnation method of the present invention adopts two impregnation treatments, respectively treating the iron-based alloy magnetic powder particles and the iron-based alloy magnetic powder core. The first impregnation treatment of the iron-based alloy magnetic powder particles can form a composite film on the surface of the magnetic powder particles, and the composite film can be bonded with nano-silicon oxide during the subsequent insulation treatment, thereby improving the density and stability of the insulation film; the second impregnation treatment of the iron-based alloy magnetic powder core, due to the presence of a large number of distributed air gaps inside the iron-based alloy magnetic powder core after pressing and annealing treatment, the impregnation liquid has good permeability and curing effect at high temperature, and can penetrate into the iron-based alloy magnetic powder core well and cure quickly, so that the method of the present invention not only ensures the coating effect of the insulating oxide, but also ensures the strength of the iron-based alloy magnetic powder core, and achieves the effect that the treated iron-based alloy magnetic powder core can greatly improve the strength of the combined magnetic circuit core while also improving its magnetic properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 The figures are scanning electron microscope images of the aerosolized sendustine magnetic powder particles after impregnation and insulation treatment and scanning electron microscope images of the cross-section of the aerosolized sendustine magnetic powder core after impregnation treatment in Example 1; wherein, (a) is a scanning electron microscope image of the aerosolized sendustine magnetic powder particles after impregnation and insulation treatment; (b) is a scanning electron microscope image of the cross-section of the aerosolized sendustine magnetic powder core after impregnation treatment. DETAILED DESCRIPTION
[0018] Example 1
[0019] The impregnation liquid for the iron-based alloy magnetic powder core of the present invention is prepared by the following method: 1kg of ferric hydroxide, 1kg of phenolic resin and 18kg of ethanol are mixed, ultrasonicated for 10 minutes, and then left to stand for 30 minutes to obtain the impregnation liquid.
[0020] The impregnation method based on the above impregnation liquid comprises the following steps: (1) 1000 g of atomized Sendust aluminum alloy powder (particle size D50 is 41 μm) before insulation is placed in an impregnation liquid for immersion for 20 min at a temperature of 40°C; after immersion, the powder is taken out and dried at a temperature of 60°C for 30 min to obtain an atomized Sendust aluminum alloy powder after impregnation; (2) adding 10 g of nano-silicon oxide dispersion (the mass concentration of the nano-silicon oxide dispersion is 4 g / L) to 1000 g of the atomized Sendust aluminum alloy powder in step (1) for insulation treatment, and then pressing and annealing to obtain an atomized Sendust aluminum alloy magnetic powder core; placing the atomized Sendust aluminum alloy magnetic powder core in acetone, washing for 10 min, and drying at a drying temperature of 60° C. to obtain an atomized Sendust aluminum alloy magnetic powder core to be impregnated; (3) completely immersing the dried aerosolized FeSiAl alloy magnetic powder core in the impregnation liquid for 2 h at a temperature of 40°C; taking it out after the immersion and washing it in acetone for 30 min; wherein the impregnation liquid is the same as the impregnation liquid in step (1); (4) The cleaned atomized Sendust aluminum alloy magnetic powder core is placed in an oven for heating and curing. The heating time is 2 hours and the heating temperature is 350°C. After natural cooling, the impregnated atomized Sendust aluminum alloy magnetic powder core is obtained.
[0021] The relative magnetic permeability of the aerosolized Sendust alloy magnetic powder core prepared in Example 1 was tested to be 62.2 at 100kHz / 1V; the DC bias performance at a magnetic field strength of 100Oe was 60.3%; the loss at 50kHz / 100mT was 221mW / cm3; and the tensile strength was 1733N.
[0022] Figure 1 (a) is a scanning electron microscope (SEM) image of the aerosolized sendustine magnetic powder particles of Example 1 after impregnation and insulation treatment; Figure 1 (a) It can be seen that the surface of the magnetic powder particles is tightly wrapped, mainly silicon oxide is bonded to the network film formed by the metal organic compound; Figure 1 (b) is a scanning electron microscope image of the cross section of the gas atomized sendust magnetic powder core obtained in Example 1 after impregnation treatment. Figure 1 (b) It can be seen that the magnetic powder particles inside the magnetic core are in close contact with each other, and the silicon oxide and the impregnation material are continuously and evenly distributed between the particles. This shows that on the one hand, the particles are well isolated, which can improve the magnetic properties of the magnetic core, and on the other hand, the particles are tightly bonded, which makes the magnetic core have good strength.
[0023] Comparative Example 1
[0024] Comparative Example 1 Compared with Example 1, the formula of the impregnation liquid is different. The impregnation liquid of Comparative Example 1 is prepared by the following method: 4 kg of epoxy resin and 16 kg of acetone are mixed, ultrasonicated for 10 minutes, and then allowed to stand for 30 minutes to obtain the impregnation liquid.
[0025] The impregnation method based on the above impregnation liquid comprises the following steps: (1) 10 g of nano-silicon oxide dispersion (the mass concentration of the nano-silicon oxide dispersion is 4 g / L) is added to 1000 g of atomized Sendust aluminum alloy powder (the particle size D50 is 41 μm) before insulation treatment, and then pressed and annealed to obtain an atomized Sendust aluminum alloy magnetic powder core; the atomized Sendust aluminum alloy magnetic powder core is placed in acetone, washed for 10 min, and dried at a drying temperature of 60°C to obtain an atomized Sendust aluminum alloy magnetic powder core to be impregnated; (2) The dried atomized FeSiAl alloy magnetic powder core is completely immersed in the impregnation liquid for 2 hours at a temperature of 40°C; after immersion, the core is taken out and cleaned in acetone for 30 minutes; (3) The cleaned atomized Sendust aluminum alloy magnetic powder core is placed in an oven for heating and curing. The heating time is 2 hours and the heating temperature is 350°C. After natural cooling, the impregnated atomized Sendust aluminum alloy magnetic powder core is obtained.
[0026] Table 1 is a comparison of the performance of the gas atomized Sendust aluminum alloy magnetic powder core obtained in Example 1 and Comparative Example 1
[0027] It can be seen from Table 1 that the overall magnetic properties of the aerosolized Sendust aluminum alloy powder core obtained by the impregnation solution and process of the present invention are improved, wherein the DC bias performance is improved by 1.6%, the loss at 50kHz / 100mT is reduced by 12.6%, and the tensile strength is increased by more than two times.
[0028] Example 2
[0029] The impregnation liquid for the iron-based alloy magnetic powder core of the present invention is prepared by the following method: 2kg of cobalt acetate, 2.7kg of polyester resin and 15.3kg of methanol are mixed, ultrasonicated for 15 minutes, and then allowed to stand for 45 minutes to obtain the impregnation liquid.
[0030] The impregnation method based on the above impregnation liquid comprises the following steps: (1) 1000 g of the sendust aluminum alloy powder (with a particle size of D50 of 56 μm) prepared by ball milling before insulation was immersed in an impregnation liquid for 40 min at a temperature of 60°C; after immersion, the powder was taken out and dried at a temperature of 90°C for 45 min to obtain the ball milled sendust aluminum alloy powder after immersion; (2) 13 g of nano-silicon oxide dispersion (the mass concentration of the nano-silicon oxide dispersion is 4 g / L) is added to 1000 g of ball-milled iron-silicon-aluminum alloy powder in step (1) for insulation treatment, and after the insulation treatment, the powder is pressed and annealed to obtain a ball-milled iron-silicon-aluminum alloy magnetic powder core; the ball-milled iron-silicon-aluminum alloy magnetic powder core is placed in acetone, washed for 12 min, and dried at a drying temperature of 90° C. to obtain a ball-milled iron-silicon-aluminum alloy magnetic powder core to be impregnated; (3) completely immersing the dried ball-milled FeSiAl alloy magnetic powder core in the impregnation liquid for 4 h at a temperature of 60°C; taking it out after immersion and washing it in acetone for 45 min; wherein the impregnation liquid is the same as the impregnation liquid in step (1); (4) The cleaned spherical milled Sendust aluminum alloy magnetic powder core is placed in an oven for heating and curing. The heating time is 4 hours and the heating temperature is 230°C. After natural cooling, the impregnated spherical milled Sendust aluminum alloy magnetic powder core is obtained.
[0031] The relative magnetic permeability of the ball-milled Sendust aluminum alloy magnetic powder core prepared in Example 2 was tested to be 71.3 at 100kHz / 1V; the DC bias performance at a magnetic field strength of 100Oe was 46.3%; the loss at 50kHz / 100mT was 269mW / cm3; and the tensile strength was 1523N.
[0032] Example 3
[0033] The impregnation liquid for the iron-based alloy magnetic powder core of the present invention is prepared by the following method: 3kg of nickel acetate, 4kg of epoxy resin and 13kg of acetone are mixed, ultrasonicated for 20 minutes, and then left to stand for 60 minutes to obtain the impregnation liquid.
[0034] The impregnation method based on the above impregnation liquid comprises the following steps: (1) 1000 g of atomized iron-silicon alloy powder (particle size D50 is 35 μm) before insulation is placed in an impregnation liquid for immersion for 60 min at a temperature of 80°C; after immersion, the powder is taken out and dried at a temperature of 120°C for 60 min to obtain an atomized iron-silicon alloy powder after impregnation; (2) adding 16 g of nano-silicon oxide dispersion (the mass concentration of the nano-silicon oxide dispersion is 4 g / L) to 1000 g of the atomized iron-silicon alloy powder in step (1) for insulation treatment, and then pressing and annealing to obtain an atomized iron-silicon alloy magnetic powder core; placing the atomized iron-silicon alloy magnetic powder core in acetone, washing for 15 min, and drying at a drying temperature of 120° C. to obtain an atomized iron-silicon alloy magnetic powder core to be impregnated; (3) completely immersing the dried aerosolized iron-silicon alloy magnetic powder core in the impregnation liquid for 6 hours at a temperature of 80°C; taking it out after the immersion, and washing it in acetone for 60 minutes; wherein the impregnation liquid is the same as the impregnation liquid in step (1); (4) The cleaned atomized iron-silicon alloy magnetic powder core is placed in an oven for heating and curing. The heating time is 6 hours and the heating temperature is 120°C. After natural cooling, the impregnated atomized iron-silicon alloy magnetic powder core is obtained.
[0035] The relative magnetic permeability of the aerosolized iron-silicon alloy magnetic powder core prepared in Example 3 was tested to be 58.2 at 100kHz / 1V; the DC bias performance at a magnetic field strength of 100Oe was 79.2%; the loss at 50kHz / 100mT was 566mW / cm3; and the tensile strength was 2615N.
[0036] Comparative Example 2 The only difference between Comparative Example 2 and Example 1 is that there is no step (1) during the impregnation process, specifically: The impregnation liquid for the iron-based alloy magnetic powder core of the present invention is prepared by the following method: 1kg of ferric hydroxide, 1kg of phenolic resin and 18kg of ethanol are mixed, ultrasonicated for 10 minutes, and then left to stand for 30 minutes to obtain the impregnation liquid.
[0037] The impregnation method based on the above impregnation liquid comprises the following steps: (1) 10 g of nano-silicon oxide dispersion (the mass concentration of the nano-silicon oxide dispersion is 4 g / L) is added to 1000 g of atomized Sendust aluminum alloy powder (the particle size D50 is 41 μm) before insulation treatment, and then pressed and annealed to obtain an atomized Sendust aluminum alloy magnetic powder core; the atomized Sendust aluminum alloy magnetic powder core is placed in acetone, washed for 10 min, and dried at a drying temperature of 60°C to obtain an atomized Sendust aluminum alloy magnetic powder core to be impregnated; (2) The dried atomized FeSiAl alloy magnetic powder core is completely immersed in the impregnation liquid for 2 hours at a temperature of 40°C; after immersion, the core is taken out and cleaned in acetone for 30 minutes; (3) The cleaned atomized Sendust aluminum alloy magnetic powder core is placed in an oven for heating and curing. The heating time is 2 hours and the heating temperature is 350°C. After natural cooling, the impregnated atomized Sendust aluminum alloy magnetic powder core is obtained.
[0038] The relative magnetic permeability of the aerosolized Sendust alloy powder core prepared in Comparative Example 2 was tested to be 61.6 at 100kHz / 1V; the DC bias performance at a magnetic field strength of 100Oe was 58.9%; the loss at 50kHz / 100mT was 233mW / cm3; and the tensile strength was 1322N.
Claims
1. An impregnation liquid for an iron-based alloy magnetic powder core, characterized in that: The invention is prepared from the following components in mass percentage: 5-15% of a metal organic compound, 5-20% of a resin and 65-90% of an organic solvent; the metal organic compound is one of ferric hydroxide, cobalt acetate or nickel acetate.
2. The impregnation liquid for the iron-based alloy magnetic powder core according to claim 1, characterized in that: The resin is one of epoxy resin, phenolic resin or polyester resin.
3. The impregnation liquid for the iron-based alloy magnetic powder core according to claim 1, characterized in that: The organic solvent is one of methanol, ethanol or acetone.
4. The impregnation method using the impregnation liquid according to claim 1, characterized in that: The steps include: (1) placing the iron-based alloy powder before insulation into an impregnation liquid for immersion, and drying after immersion to obtain the iron-based alloy powder after immersion; (2) insulating the iron-based alloy powder of step (1) with a nano-silicon oxide dispersion, and preparing an iron-based alloy magnetic powder core by a powder metallurgy process after the insulation treatment to obtain an iron-based alloy magnetic powder core; washing and drying the obtained iron-based alloy magnetic powder core to obtain an iron-based alloy magnetic powder core to be impregnated; (3) completely immersing the iron-based alloy magnetic powder core of step (2) in the impregnation liquid, and then washing it; (4) The cleaned iron-based alloy magnetic powder core is heated and solidified, and then naturally cooled to obtain an impregnated iron-based alloy magnetic powder core.
5. The impregnation method according to claim 4, characterized in that: In step (1), the soaking temperature is 40-80°C, and the soaking time is 20-60 min; the drying temperature is 60-120°C, and the drying time is 30-60 min.
6. The impregnation method according to claim 4, characterized in that: In step (2), the amount of nano-silicon oxide dispersion added is 10-16‰ of the mass of the iron-based alloy powder.
7. The impregnation method according to claim 4, characterized in that: In step (2), the iron-based alloy magnetic powder core is cleaned with acetone for 10 to 15 minutes; the drying temperature is 60 to 120°C.
8. The impregnation method according to claim 4, characterized in that: In step (3), the soaking time is 2 to 6 hours, and the soaking temperature is 40 to 80° C.; the iron-based alloy magnetic powder core after soaking is cleaned with acetone, and the cleaning time is 30 to 60 minutes.
9. The impregnation method according to claim 4, characterized in that: In step (4), the heating time is 2 to 6 hours, and the heating temperature is 120°C to 350°C.
Citation Information
Patent Citations
Anti-rust treatment method for iron-based alloy magnetic powder core
CN113539661A
Preparation method of iron-silicon soft magnetic powder core for improving strength of green body and finished product magnetic core
CN115910583A
Impregnation liquid and application thereof as well as preparation method and application of magnetic powder core
CN115966360A
Method for improving mechanical strength of iron-based alloy magnetic powder core
CN116403821A
Preparation method of oxidation-resistant high-resistivity soft magnetic composite material
CN119340056A
Cited By
Impregnation liquid and impregnation process for soft magnetic core
CN121148884A